Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1128/jvi.02487-16
|View full text |Cite
|
Sign up to set email alerts
|

Defining a Novel Role for the Coxsackievirus and Adenovirus Receptor in Human Adenovirus Serotype 5 Transduction In Vitro in the Presence of Mouse Serum

Abstract: Human adenoviral serotype 5 (HAdV-5) vectors have predominantly hepatic tropism when delivered intravascularly, resulting in immune activation and toxicity. Coagulation factor X (FX) binding to HAdV-5 mediates liver transduction and provides protection from virion neutralization in mice. FX is dispensable for liver transduction in mice lacking IgM antibodies or complement, suggesting that alternative transduction pathways exist. To identify novel factor(s) mediating HAdV-5 FX-independent entry, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 65 publications
(130 reference statements)
2
11
0
Order By: Relevance
“…Interestingly, murine sera from different immunoglobulin-deficient mice strains ( Rag2 -/- , Ighm tm1Che ), behaved in a similar manner, suggesting that at least some of the complement molecules directly attach to HAdV-5 capsids without requiring the presence of immunoglobulins (Figure 3). Furthermore, HAdV-5 was neutralized by immunocompetent C57BL/6 serum in the absence of FX, as previously demonstrated [11,21]. However, regardless of the presence of FX, some of the molecules involved in the immune response were able to bind to the virions.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Interestingly, murine sera from different immunoglobulin-deficient mice strains ( Rag2 -/- , Ighm tm1Che ), behaved in a similar manner, suggesting that at least some of the complement molecules directly attach to HAdV-5 capsids without requiring the presence of immunoglobulins (Figure 3). Furthermore, HAdV-5 was neutralized by immunocompetent C57BL/6 serum in the absence of FX, as previously demonstrated [11,21]. However, regardless of the presence of FX, some of the molecules involved in the immune response were able to bind to the virions.…”
Section: Discussionsupporting
confidence: 72%
“…It has been previously reported that HAdV-5 specifically binds to murine and human FX, and that the capsid:FX interaction inhibits the neutralization mediated by IgM and complement components [11,21]. A previous study based on particle size tracking demonstrated that purified human IgM and IgG were able to bind to HAdV-5 virions, with IgM only binding in a FX-dependent manner [14].…”
Section: Discussionmentioning
confidence: 99%
“…The shield might also block a soluble blood factor that binds to the virion and retargets the particle to CAR-expressing tissue. Recently, the presence of such a factor has been described, but not identified, in murine Rag2 -/- serum 56 . In conclusion, the combination of retargeting and shielding improved the tumor-to-liver ratio upon intratumoral injection from 300 to 7200 for the EGFR + and from 1300 to 1,100,000 for the HER2 + xenograft.…”
Section: Discussionmentioning
confidence: 98%
“…Most AdVs have one unique fibre that attaches to variable cellular receptors. HAdV-2 and HAdV-5 in subgroup C use the high-affinity human coxsackie and adenovirus receptor (CAR) as the cellular receptor to infect host cells [13,14], HAdV-37 uses integrins to infect human corneal cells [15], mouse adenovirus type 1 utilizes integrin and heparin sulfate as cellular receptors [16], bovine adenovirus serotype 3 utilizes sialic acid as a receptor for viral entry [17], and porcine adenovirus serotype 3 internalization is independent of CAR and integrin, but uses some other receptors [18]. However, HAdV-52, HAdV-40 [19], and HAdV-41 [20] are equipped with two different fibre proteins, only the long fibre type is inserted into each penton and binds the CAR, whereas the short fibre binds to sialylated glycoproteins during infection [21,22].…”
Section: Introductionmentioning
confidence: 99%